Ethnobotanical Study of Medicinal Plants Used in the Northeast Latrine Zone of Persian Gulf - M Dolatkhahi; I Nabipour (Institue of Medicinal Plants, ACECR, 2014)
Background: Nowadays, medicinal plants are widely used in remedies of several ailments and improvement of human health because of their pharmaceutical properties. Objective: Recognition of plant species and data collection of native inhabitants in the case of attribute and either preparation methods of them in the treatment of various diseases. Methods: In order to gather information on medicinal species the area, an investigation was performed during 2011-2013. Data was obtained using direct interviews with 120 informants particularly those who were more familiar with the herbs and their medicinal properties. The most widely plant used and also the most populous families and genera in the region were identified. Results: Results of this study indicated that this zone has 70 plant species which belong to 37 families and 62 genera. Among 37 plant families being used in this area, Asteraceae with 7 species is the most used family and Plantago with 4 species is the largest genus in this zone. Intestinal - digestive system is the first target for traditional medicine in the area. Conclusion: In general, our findings can be used as a basis for selecting useful medicinal plants for further pharmacological and phytochemical studies and consequently to discover new drugs.